UPAYA OPTIMALISASI KEMAMPUAN ENTREPRENEURSHIP ERA DIGITAL - Safar Nasir, Muhammad; Saleh, Rahmat; Yuniarti, Dini (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Education and training are still needed to improve digital literacy and entrepreneurial skills. This community service must prepare and equip prospective entrepreneurs to take advantage of opportunities better and face challenges in the digital era. The service method applies survey observations to ensure the number of achievements and the achievement of participation conditions in activities supported by pre-test observations as the primary material for FGDs. It ends with an evaluation in the form of a post-test. The abstract should end with comments on the importance of the results or a brief conclusion. Overall, the training on entre preneurship in the digital era has significantly improved participants' knowledge, skills, and attitudes. Participants demonstrated compreh ensive understand ing, practical skills, and high motivation to apply digital entrepreneur ship concepts in starting or expanding their businesses. Although participants have concrete follow-up plans, it is important that there is a structured mentoring mechanism to ensure the realization of these plans and that closer collaboration with relevant parties is needed to support post-training digital business development.